AB0415 Four Years of Experience with Quantiferon-TB Gold Test in Patients with Biological Treatment. (9th June 2015) - Zanova, E.; Kozakova, D.; Rybar, I.; Solovic, I.; Rovensky, J.
Abstract : Background: Therapeutic blocade of tumor necrosis factor alpha (TNF-α) is an effective treatment in immune-mediated inflamatory diseases. However, biologic anti-TNF therapy can reactivate latent tuberculosis infection (LTBI). Testing the presence of LTBI by IGRA tests (QuantiFERON-TB Gold, T.Spot-TB) has recently become a necessary part of the diagnostic screening in patients with biological treatment. The results of IGRAs may be positive, negative or indeterminate. Conversion of initially negative test result to positive may represent reactivation of LTBI or active tuberculosis. Objectives: To evaluate results of QuantiFERON-TB Gold test (QFT-G) in patients receiving biological therapy in connection with biologicals in the period 2011-2014. Methods: LTBI in the blood of patients with rheumatoid arthritis, ankylosing spondylitis and psoriatic arthritis was detected using QuantiFERON-TB Gold test (ELISA, QIAGEN). Total number of assays performed using QFT-G over 4 years was 4 482. All patients fulfilled the diagnostic criteria for biological treatment with anti- TNF-α and anti-IL6 blockers (adalimumab, golimumab, etanercept, tocilizumab). Results: The number of repeatedly positive QFT-G results in the years 2011-2014 was 2.92% (131/4482). The number of positive QFT-G results in the initial determination was 3.28% (147/4482) of the total determination of QFT-G and number of conversion of QFT-G was 1, 4% (63/4482) and 18, 47% to 341 (the total number of positive QFT-G). The summary results of QFT-G conversions during the biological treatment in 2011-2014 was 63 patients - in anti-TNF-α is 43 (68%) and anti IL-6 11 (18, 9%), other biologicals 9 (14%). We monitored changes in the levels of the cytokine interferon gamma (IFN-γ) in 2012. In his evidence and quantification based IGRA tests. The concentration of IFN-γ before and after QFT-G conversion in the parameter (TB-Nil)* showed 14.4 fold increase in anti-IL-6, and 91.1 fold increase in anti-TNF-α blockers. Increasing levels of IFN-γ in the parameter (Mit-Nil)* was constant in all evaluated biologicals (1.5-fold). In the group of patients with permanent positive QFT-G were found changes in the concentration of IFN-γ in any parameter before and during biological treatment. Conclusions: The total number of positive QFT-G results corresponds to data from available sources, although the percentage of primary positives QFT-G is relatively high. The number of QFT-G conversions over 3 years showed a downward trend, in 2014 has continued to increase. The results in the group of patients with anti-TNF-α therapy confirm the increased risk of activation LTBI. The number of QFT-G conversions in patients with anti-TNF therapy and in a group of patients with other biologicals, studied in 2013, does not present a significant differences and responds to the total number of patients in individual groups. Monitoring of IFN-γ concentrations during the biological treatment could find application in the assessment of the effect of various biologicals. Disclosure of Interest: None declared